Sixty years of life with François Gros - Scherrer, Klaus (Comptes Rendus Biologies)
This is meant to be a personal account of my relationship with François Gros who, as the director of the laboratory where I had my first team became a close and fatherly friend. Over 60 years we had permanent interactions, whether close or far away. And I wish to revive here some of our relation at the grassroots, as well as the folklore in and around his laboratory. He was not only an excellent scientist but also a Statesman of Science and beyond. Myself a minor figure in his big endeavors, this aspect of his life I just observed from below but with much empathy. All along he considered our experimental data and ideas realistic while they were rejected as iconoclastic by the many others. Being taken seriously as a researcher, I did not participate in his professional networks because I never fit the necessary profile in terms of scientific consensus. But his friendship was a major and basic element in my scientific and personal life; I hope my report hereafter does justice to his personality and immense merits.